2014
DOI: 10.1038/bjc.2013.830
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR7 extends survival following irradiation of brain tumours in mice and rats

Abstract: Background:In experimental models of glioblastoma multiforme (GBM), irradiation (IR) induces local expression of the chemokine CXCL12/SDF-1, which promotes tumour recurrence. The role of CXCR7, the high-affinity receptor for CXCL12, in the tumour's response to IR has not been addressed.Methods:We tested CXCR7 inhibitors for their effects on tumour growth and/or animal survival post IR in three rodent GBM models. We used immunohistochemistry to determine where CXCR7 protein is expressed in the tumours and in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 50 publications
(71 reference statements)
6
59
0
Order By: Relevance
“…In 2008, Plerixafor gained Food and Drug Administration approval for mobilization of hematopoietic stem cell transplants in non-Hodgkin lymphoma and multiple myeloma (18), making CXCR4 the second chemokine receptor (in addition to CCR5) to be the target of a marketed drug. Small molecule inhibitors of ACKR3 are extensively studied because of their ability to block tumor reappearance in experimental models of glioblastoma multiforme (19). Finally, chemokine-based inhibitors also show therapeutic promise (20,21); for example, P2G-CXCL12, an antagonist variant of CXCL12, was demonstrated to slow the progression of experimental autoimmune encephalomyelitis (EAE), a murine model of multiple sclerosis (21).…”
Section: Cxcr4mentioning
confidence: 99%
“…In 2008, Plerixafor gained Food and Drug Administration approval for mobilization of hematopoietic stem cell transplants in non-Hodgkin lymphoma and multiple myeloma (18), making CXCR4 the second chemokine receptor (in addition to CCR5) to be the target of a marketed drug. Small molecule inhibitors of ACKR3 are extensively studied because of their ability to block tumor reappearance in experimental models of glioblastoma multiforme (19). Finally, chemokine-based inhibitors also show therapeutic promise (20,21); for example, P2G-CXCL12, an antagonist variant of CXCL12, was demonstrated to slow the progression of experimental autoimmune encephalomyelitis (EAE), a murine model of multiple sclerosis (21).…”
Section: Cxcr4mentioning
confidence: 99%
“…Previous results focusing on the expression of both receptors in human GBM indeed yielded an expression of CXCR4 by a subpopulation of GBM cells with stem cell properties (14), whereas the bulk of more differentiated GBM cells express CXCR7 (15,24). Conversely, other studies reported the existence of CXCR4-CXCR7 double-positive cells and showed that this subpopulation might regulate the stem cell phenotype (25), and was able to initiate intracranial tumors in vivo (26). Nevertheless, also CXCR4 and CXCR7 single populations exist and a high level of heterogeneity in both the surface expression and functions of CXCR4 and CXCR7 in primary human GBM cells of the proliferative subclass was determined (26).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, also CXCR4 and CXCR7 single populations exist and a high level of heterogeneity in both the surface expression and functions of CXCR4 and CXCR7 in primary human GBM cells of the proliferative subclass was determined (26). In addition, GBM primary cell cultures show a heterogeneous cell surface expression of CXCR4 and CXCR7 despite similar levels of corresponding mRNAs (25), and the expression of CXCR4 and CXCR7 is significantly correlated (19).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the CXCL12-CXCR4/ CXCR7 axis in GSCs radioresistance has been strengthened by the recent observation that CXCR7 blockade after irradiation signifi cantly reduced tumor growth and relapse, and enhanced survival in a xenograft model of glioblastoma, likely affecting GSCs [ 179 ].…”
Section: Cxcl12-cxcr4/cxcr7 Axismentioning
confidence: 99%